A novel membrane distillation response technology for nucleation detection, metastable zone width measurement and analysis. (29th September 2015) - Jiang, Xiaobin; Ruan, Xuehua; Xiao, Wu; Lu, Dapeng; He, Gaohong
Abstract: In this paper, a novel metastable zone width (MSZW) analysis technology was proposed. This membrane distillation-response (MDR) technology was established on a response mechanism in which the transmembrane flux sharply decreased when the crystals nucleated on the pores of the microporous membrane interface. The robustness and effectiveness of the proposed technology were established by comparing its performance with the conventional optical technology (laser intensity response, LIR), while, the MDR technology had the advantage of detecting the nucleation in optically opaque solution compared to LIR. Detailed simulations on several typical binary aqueous solution systems were implemented to represent the role of T f, T p and A / V 0 on the supersaturation degree modification. The simulative results revealed the other advantages of MDR for controlling accuracy and flexibility during MSZW measurement. This technology could provide meaningful original data for the process design and optimization of typical and novel crystallization processes. Highlights: Novel MSZW measurement approach (membrane distillation response, MDR) was proposed. MDR yielded good results especially for the measurement of optically opaque system. MDR has the advantages of controlling accuracy and flexibility. MDR provides original data for typical and novel crystallization optimization.